2018
DOI: 10.1002/jum.14571
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Ultrasound in Undergraduate Urology Education: A Prospective Control‐Intervention Study

Abstract: Point-of-care US training complements standard undergraduate classroom teaching of urology. Students effectively learned the skills to apply point-of-care US in their assessment of patients, and this process did not interfere with achieving the course objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…McGill University started its comprehensive longitudinal POCUS curriculum in 2013 and expanded its simulation-based POCUS training in 2017 [ 25 ]. The University of Saskatchewan, since 2018, has published on a number of their innovative medical student POCUS education initiatives [ 26 , 27 ]. More recently the University of Ottawa published the results of on their pre-clerkship POCUS training [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…McGill University started its comprehensive longitudinal POCUS curriculum in 2013 and expanded its simulation-based POCUS training in 2017 [ 25 ]. The University of Saskatchewan, since 2018, has published on a number of their innovative medical student POCUS education initiatives [ 26 , 27 ]. More recently the University of Ottawa published the results of on their pre-clerkship POCUS training [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In renal and bladder ultrasound, integration of ultrasound training focusing on flank pain and voiding difficulty into a clinical skill course allowed medical students to learn a new set of clinical skills. The method did not distract them from their traditional curriculum education [ 53 ]. In assessing the abdominal aorta, 62% of medical students with no prior experience in ultrasound who participated in a short training program were able to accurately measure the maximal diameter of the abdominal aorta, reaching a professional standard of skill [ 54 ].…”
Section: Gaining An Understanding Of Ultrasound and Fostering Technical Skillsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] One medical school in Canada found that integration of ultrasound into their renal basic science course helped students achieve course objectives, but their curriculum has not been published. 25 Thus, we share our pilot renal POCUS curriculum for preclerkship medical students that educators can adapt and apply at their own institutions.…”
Section: Introductionmentioning
confidence: 99%